1998
DOI: 10.1128/iai.66.12.6045-6048.1998
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Glycosaminoglycan Recognition by the Lyme Disease Spirochete, Borrelia burgdorferi

Abstract: Borrelia burgdorferi, the Lyme disease agent, binds glycosaminoglycans (GAGs) such as heparin, heparan sulfate, and dermatan sulfate. Heparin or heparan sulfate fractions separated by size or charge were tested for their ability to inhibit attachment ofB. burgdorferi to Vero cells. GAG chains of increasing length and/or charge showed increasing inhibitory potency, and detectable heparin inhibition of bacterial binding required a minimum of 16 residues. The ability of a given heparin fraction to inhibit binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
(44 reference statements)
5
29
0
Order By: Relevance
“…If Bgp promotes bacterial attachment to GAGs expressed on the surface of mammalian cells, exogenous Bgp should inhibit cell attachment. We previously showed that bacterial attachment to 293, Vero and C6 cells was mediated by GAGs (Leong et al, 1998b;Parveen et al, 1999). Therefore, we incubated monolayers of 293, Vero and C6 cells with recombinant Bgp (cleaved from GST-Bgp) prior to the addition of radiolabelled bacteria and Fig.…”
Section: Recombinant Bgp Inhibits Bacterial Attachment To Mammalian Cmentioning
confidence: 99%
See 2 more Smart Citations
“…If Bgp promotes bacterial attachment to GAGs expressed on the surface of mammalian cells, exogenous Bgp should inhibit cell attachment. We previously showed that bacterial attachment to 293, Vero and C6 cells was mediated by GAGs (Leong et al, 1998b;Parveen et al, 1999). Therefore, we incubated monolayers of 293, Vero and C6 cells with recombinant Bgp (cleaved from GST-Bgp) prior to the addition of radiolabelled bacteria and Fig.…”
Section: Recombinant Bgp Inhibits Bacterial Attachment To Mammalian Cmentioning
confidence: 99%
“…Although a contribution of the core protein component of proteoglycans towards bacterial recognition in these experiments cannot be ruled out, current evidence suggests that polysaccharide moieties play the major role. For example, a relatively small segment of the GAG chain (16 residues) effectively inhibited bacterial attachment (Leong et al, 1998b). B. burgdorferi is also able to agglutinate trypsinized and fixed erythrocytes (Leong et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferential localization in the loose connective tissue spaces between the collagen fiber bundles may reflect the well‐known binding affinity of the spirochetes to components of the extracellular matrix, especially proteoglycans(39–41). It is tempting to speculate that the low tissue turnover of collagenous connective tissue coupled with the paucity of immune effector cells may contribute to the persistence of Bb in this immunologically privileged site.…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed mutagenesis of wildtype B subunit was carried out using standard kits and following the manufacturer's instructions. After mutagenesis of the TGT cysteine codon to the TCT serine codon the entire gene was sequenced and found to be otherwise identical to the published sequence [5].…”
Section: Bacteriamentioning
confidence: 99%